Indigenous Resilience in Australia: A Scoping Review Using a Reflective Decolonizing Collective Dialogue - Usher, Kim; Jackson, Debra; Walker, Roz; Durkin, Joanne; Smallwood, Reakeeta; Robinson, Melanie; Sampson, Uncle Neville; Adams, Isabelle; Porter, Cheryl; Marriott, Rhonda (Frontiers in Public Health, 2021)
Contemporary definitions and understandings of resilience refer to an individual's positive adaptation to the experience of adversity. One of the challenges of this extant body of work is that the central concept of resilience is rarely questioned. Current understandings of these concepts, largely framed in Western understandings, are unquestioningly accepted, reframed for, yet not by, Indigenous peoples, and then are unchallenged when imposed on Indigenous peoples. A scoping review was conducted and reported in line with the PRISMA-ScR guidelines. The review involved the participation of local Aboriginal Research Cultural Advisory Groups who participated and approved the analysis of the findings and collaborated on the design and writing of the paper. Eight publications drew on Aboriginal constructs of resilience in examining the effectiveness of programs, processes, and practices to promote individual and/or collective resilience and well-being. Most studies emphasized the need for strategies to strengthen individual or community connection to culture to foster resilience. Six studies used culturally validated strength-based tools to measure resilience, while two relied on Western constructs. This review reveals both the distinctive colonial characteristics of adversity experienced by Aboriginal people and the range of coping strategies and protective resources that support the development of resilience within different Aboriginal communities in diverse research sites across Australia. Importantly, many studies confirm adversity is linked to the enduring legacies of colonization, continuous and cumulative transgenerational grief and loss, structural inequities, racism, and discrimination. These external factors of adversity are unique to Aboriginal populations, as are the protective factors that entail strengthening connection to culture (including language reclamation), community, ancestry and land (including management and economic development) which contribute to individual and collective resilience. These findings suggest that Aboriginal community resilience is strengthened through the collective experience of adversity, such as transgenerational grief and loss, and the resulting support structures and shared resources that are developed and maintained through cultural practices to strengthen the bonds and mutual reciprocity to participate in transformative strategies to address adversity. This review highlights that strategies such as building on community strengths, capacities, and resources is critical when strengthening resilience within Indigenous communities across Australia.